Deaths in Immigration and Customs Enforcement (ICE) detention: FY2018-2020 - Sophie Terp; Sameer Ahmed; Elizabeth Burner; Madeline Ross; Molly Grassini; Briah Fischer; Parveen Parmar (AIMS Press, 2021)
Background: Many civil liberties organizations have raised concerns that substandard medical care in United States Immigration and Customs Enforcement (ICE) detention facilities have led to preventable deaths. The 2018 Department of Homeland Security Appropriations Bill required ICE to make public all reports regarding in-custody deaths within 90 days beginning in Fiscal Year (FY) 2018. Accordingly, ICE has released death reports following each in-custody death since April of 2018. This study describes characteristics of deaths among individuals in ICE detention following the FY2018 mandate. Methods: Data was extracted from death reports published by ICE following the FY2018 mandate. Causes of death were categorized as suicide or medical, and medical deaths as COVID-19-related or not. Characteristics were compared between medical and suicide deaths, and among medical deaths between COVID-19-related and non-COVID-19-related deaths. Additionally, death rates per person-year and per 100,000 admissions were calculated for FY2018, 2019, and 2020 using methods from prior work evaluating deaths among detained immigrants in the United States. Results: Since April 2018, 35 individuals have died in ICE detention. The death rate per 100,000 admissions in ICE detention was 2.303 in FY2018, 1.499 in FY2019, and 10.833 in FY2020. Suicide by hanging was identified as the cause of death in 9 (25.7%), and medical causes in the remaining 26 (74.3%). Among 26 deaths attributable to medical causes, 8 (30.8%) were attributed to COVID-19, representing 72.7% of 11 deaths occurring since April 2020. Conclusions: The death rate among individuals in ICE detention is increasing amidst the COVID-19 pandemic. Potentially preventable causes of death including COVID-19 and suicide contribute to at least half of recent deaths. Findings suggest that individuals detained by ICE may benefit from improved psychiatric care and prevention measures to combat suicide, as well as increased infection control efforts to reduce mortality associated with COVID-19.